Collections of the Bristol Record Office (as filmed by the AJCP) [M1919] - Australian Joint Copying Project; National Library of Australia; State Library of New South Wales; Bristol Record Office (Canberra : Australian Joint Copying Project, 1950)
1. Contracts for the passage of paupers to Van Diemen's Land and N.S.W., 1833. 2. Correspondence between Sir George Chick, Bristol and James B. Gibbs, Vic. and S.A., 1855-61 re family and success at goldfields. 3. Documents re death of Henry J. Player, storekeeper at Mansfield, Vic. 4. Letter, E.G. Masey, Paterson River, N.S.W. to E. Masey, Bristol, 1847. 5. Certificate of competence as engine driver granted to Richard Murray, W.A., 1897-6. Regulations for disposal of land, preliminary sales of land and emigration of labourers (South Australia) 1835. 7. Letters of Daniel R. Long, 1840-41 and Susannah M. Long, 1849 re Melbourne. 8. Bill of exchange, 1861. 9. Description of lights made for Christ Church Cathedral, Ballarat. 10. Journal of passengers on voyage of S.S. Great Britain to Melbourne, 1852. 11. Correspondence of Clement and Chandler families, 1848-1879 re Australia. 12. Will of John Acraman of Adelaide, 1905 and extract on John Acraman from "The pastoral pioneers of South Australia".
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project miscellaneous series M1919.
Also available online
Microfilm copy of originals held by Bristol Record Office.
Descriptive list available (3 p.).
Keywords: Immigrants -- Australia -- Archives; Australia -- Description and travel -- 19th century; Australia -- Social conditions -- 19th century